The Effect of social interaction on theory of mind - Somerville, Jacqueline (My University, 2006)
The purpose of this study was to determine whether there was a relationship between attendance at daycare facilities and theory of mind ability. In addition to investigating the relationship between daycare and theory of mind, sibling relationships were also examined. The two sibling relationships investigated were having any siblings, and having only older siblings. The participants were 35, Caucasian, nursery-attending children, between the ages of 3 and 5 years, from working and middle-class families in Scotland. All participants had a questionnaire completed on their behalf, by a parent or guardian, which collected information regarding their sibling status and daycare history. Theory of mind ability was tested using three false belief tasks, including one unexpected contents task, one change of location task, and one deception task. The data, controlling for age, did not show a link between daycare and theory of mind ability, either through correlations or analysis of variance tests. Furthermore, there was found to be no significant relationship between siblings and theory of mind ability.
Keywords: social interaction; theory of mind; children in daycare; sibling relationships; false belief tasks